Evaluating Food Safety and Profitability Challenges in the Dayok Production Chain in General Santos City - Lapinig, Eujeny Marie; Ayoc, Renjil; Adol, Judith (International Journal of Research in Interdisciplinary Studies, 2026)
This case study analyzed the challenges and opportunities regarding food safety and profitability in the Dayok production chain in General Santos City. Using a descriptive quantitative research approach, which is based on surveys from Dayok producers and retailers, the analysis has detected key factors affecting production practices, market performance, and income generation. The results show that producers face problems related to sanitation, the absence of standardized methods of processing, and limited access to appropriate facilities. Additionally, fluctuations in market prices have also challenged the production environment. Retailers experience problems maintaining product quality and ensuring safety while generating profits due to tough competition and uncertainty of supply. Opportunities for improved hygiene practices, value addition, training, government regulatory reforms, and increased government support have been indicated. The study has emphasized the need for teamwork among producers, retailers, and local authorities in order to enhance the safety, profitability, and sustainability of the Dayok industry in General Santos City.